Building Relational Understanding through Hypothetical Learning Trajectory of Probability - Rahmi, Fathur; Sampoerno, Pinta Deniyanti; Ambarwati, Lukita (International Journal of Elementary Education, 2021)
Many researchers found that students had difficulty in understanding probability material. Students mostly focus on applying formulas to find solutions to problems without knowing what the concept is and why the formula works. This underlies the researcher to design probability learning as a hypothetical learning trajectory. The study aims to describe a series of learning activities designed to build relational understanding skills in probability material. This study uses a design research method consisting of three stages, namely preparation and design, teaching experiment, and retrospective analysis. Data collection techniques were carried out using a video recorder, documentation, and test questions. The data collected is in the form of qualitative data. The collected data is interpreted by peers, teachers, and supervisors to reduce the subjectivity of the researcher's point of view. All data that has been collected were analyzed retrospectively. The results of the research conducted showed that students experienced an increase and gave a good response in solving problems. Teachers are expected to use a learning design with a realistic mathematical approach because it helps students understand learning and apply their knowledge in everyday life.